2020
DOI: 10.1101/2020.12.20.423717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual conflict drives micro- and macroevolution of sexual dimorphism in immunity

Abstract: Sexual dimorphism in immunity is believed to reflect sex-differences in trade-offs between competing life history demands. Sexual selection can have major effects on mating rates and sex-specific costs of mating and may thereby influence sex-differences in immunity as well as associated host-pathogen dynamics. Yet, experimental data linking the mating system to evolved sexual dimorphism in immunity are scarce and the direct effects of mating rate on immunity are not well established. Here, we use transcriptomi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 136 publications
(355 reference statements)
3
13
0
Order By: Relevance
“…First, our phenotypic engineering experiment confirmed that shortening of these male-benefit spines has a direct positive effect on female fitness, previously only inferred from comparative studies [26,27]. Previous work has demonstrated that the spines cause injuries to the female reproductive tract [24,25,37] and induce an immune response in females [27,28,42]. Genital spine length in males is correlated with female reproductive tract morphology across populations [27] and species [26], where an evolutionary thickening of the reproductive tract is associated with longer spines.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…First, our phenotypic engineering experiment confirmed that shortening of these male-benefit spines has a direct positive effect on female fitness, previously only inferred from comparative studies [26,27]. Previous work has demonstrated that the spines cause injuries to the female reproductive tract [24,25,37] and induce an immune response in females [27,28,42]. Genital spine length in males is correlated with female reproductive tract morphology across populations [27] and species [26], where an evolutionary thickening of the reproductive tract is associated with longer spines.…”
Section: Discussionsupporting
confidence: 84%
“…This shared life-history trade-off scenario is supported by the positive direct effects of L males on female fecundity and by the negative genetic correlation between body size and spine length in males, but less so by the positive genetic correlation between female body size and male spine length (electronic supplementary material). It is also consistent with the fact that primary sexual traits in males and females show correlated evolution across Callosobruchus species [62] and comparative data suggest trade-offs between investment in primary sexual traits and other competing life-history demands, such as immunity [28], in this genus [55]. Irrespective of the underlying genetic mechanism, however, our results show that genetic variation associated with spine length in males is positively related to genetic variation in female lifetime offspring production, under the conditions in which our assays were performed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In both these studies (one on the flour beetle Tribolium castaneum and the other on the seed beetle Callosobruchus maculatus; (Hangartner et al , 2015;Bagchi et al , 2021 respectively)), females from polygamous populations had higher levels of PO than females from monogamous populations, with no effect on males from either of the two experimental regimes. The higher levels of PO in females from sexually selected populations did not influence pathogen clearance in either study, although in one of the studies higher PO activity was correlated with lower survival in females upon bacterial infection (Bagchi et al , 2021). These studies indicate how sexual selection and sexual conflict can drive sex-specific differences in male and female immunity.…”
Section: Introductionmentioning
confidence: 64%
“…Selection for improved immunity (including better physiological responses to immune challenges) in experimental populations has generally resulted in a robust and rapid response (Armitage & Siva-Jothy, 2005;Martins et al , 2013;Joop et al , 2014;Ferro et al , 2019). Two studies that explored the effect of sexual selection on immunity by experimentally evolving populations with and without sexual selection have found that males and females diverge in their investment in innate immunity (measured as phenyloxidase activity; PO) (Hangartner et al , 2015;Bagchi et al , 2021). In both these studies (one on the flour beetle Tribolium castaneum and the other on the seed beetle Callosobruchus maculatus; (Hangartner et al , 2015;Bagchi et al , 2021 respectively)), females from polygamous populations had higher levels of PO than females from monogamous populations, with no effect on males from either of the two experimental regimes.…”
Section: Introductionmentioning
confidence: 99%